Exploring parents' provision of factors related to the establishment of physical activity between normal weight and overweight infants. Issue 3 (28th October 2020) - Dinkel, Danae; Rech, John P.; Snyder, Kailey
Abstract: Purpose: Infancy is a critical time for the prevention of obesity and establishment of healthy behaviors such as physical activity that help to control weight. A limited amount of research has examined if factors related to infant physical activity vary by infant weight status. Therefore, the purpose of this mixed methods triangulation study was to examine differences in motor development, the home environment, and infant‐parent play behaviors as well as to explore how parents promote active play opportunities with normal weight infants (NWIs) and overweight infants (OWIs). Design and Methods: We used a mixed methods triangulated approach to combine quantitative and qualitative data strands to examine variables associated with active play in normal weight ( n = 16) and overweight ( n = 11) infants. Data were analyzed using a two‐tailed Mann–Whitney U nonparametric test and a summative content analysis approach. Results: Although there were no differences in infants' motor development and parent play behaviors based on infant weight, several other differences were found. OWIs had less access to materials that stimulate locomotor movement. Further, parents of OWIs more often reported utilizing cognitive play strategies in comparison to parents of NWIs who more often reported using physical play strategies. Parents felt they were the greatest influence on their child's activity regardless of infant size. Importantly, all parents desired more specific guidelines on how to encourage active play and preferred this information was delivered by their healthcare provider. Practice Implications: To meet parents' desires and potentially improve infants' developmental outcomes through the establishment of healthy physical activity behaviors, pediatric nurses could provide more specific guidance on providing active opportunities for infants.